Dynamical Tuning of Nanowire Lasing Spectra - Zapf, Maximilian; Roeder, Robert; Winkler, Karl; Kaden, Lisa; Greil, Johannes; Wille, Marcel; Grundmann, Marius; Schmidt-Grund, Ruediger; Lugstein, Alois; Ronning, Carsten (Nano Letters, 2017)
Realizing visionary concepts of integrated photonic circuits, nanospectroscopy, and nanosensing will tremendously benefit from dynamically tunable coherent light sources with lateral dimensions on the subwavelength scale. Therefore, we demonstrate an individual nanowire laser based device which can be gradually tuned by reversible length changes of the nanowire such that uniaxial tensile stress is applied to the respective semiconductor gain material. By straining the device, the spontaneous excitonic emission of the nanowire shifts to lower energies caused by the bandgap reduction of the semiconductor. Moreover, the optical gain spectrum of the nanolaser can be precisely strain-tuned in the high excitation regime. The tuning of the emission does not affect the laser threshold of the device, which is very beneficial for practical applications. The applied length change furthermore adjusts the laser resonances inducing a redshift of the longitudinal modes. Thus, this concept of gradually and dynamically tunable nanolasers enables controlling and modulating the coherent emission on the nanoscale without changing macroscopic ambient conditions. This concept holds therefore huge impact on nanophotonic switches and photonic circuit technology.
CRIS-Team Scopus Importer:2023-04-20
Keywords: bandgap modification; cadmium sulfide; emission tuning; lasing; Nanowire; strain